1998
DOI: 10.1111/j.1399-6576.1998.tb05350.x
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of nausea and vomiting with granisetron, droperidol and metoclopramide during and after spinal anaesthesia for caesarean section: A randomized, double‐blind, placebo‐controlled trial

Abstract: Granisetron is highly effective for preventing nausea and vomiting during and after spinal anaesthesia for caesarean section. Droperidol and metoclopramide are effective for the prevention of intraoperative, post-delivery emesis, but are ineffective for the reduction of the incidence of postoperative emesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 12 publications
1
16
2
Order By: Relevance
“…13,14 We believe this is why the incidence of nausea in the sodium-citrate-treated patients (7-37%) was lower than the incidence reported in other studies (63-76%). 6,7 The results of our study differ from those of the only other randomized study on this subject. Palmer et al found that oral Bicitra® did not affect the incidence of nausea during Cesarean delivery.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…13,14 We believe this is why the incidence of nausea in the sodium-citrate-treated patients (7-37%) was lower than the incidence reported in other studies (63-76%). 6,7 The results of our study differ from those of the only other randomized study on this subject. Palmer et al found that oral Bicitra® did not affect the incidence of nausea during Cesarean delivery.…”
Section: Discussioncontrasting
confidence: 97%
“…[3][4][5] Although sodium citrate is commonly used, many patients dislike its taste and some patients complain of nausea. 6,7 We hypothesized that women having elective Cesarean delivery under spinal anesthesia would have a higher incidence of nausea when receiving sodium citrate rather than water and famotidine immediately prior to surgery. We designed a randomized trial to test this hypothesis.…”
Section: Objectifmentioning
confidence: 99%
“…The incidence of intraoperative postdelivery emetic symptoms was lower in our study (43.8%) than that reported by Fujii et al (63%) [10], but higher than that reported by Baliki et al (17%) [11]. The overall incidence of intraoperative nausea and emesis during regional anesthesia for cesarean section is extremely variable and can reach 79%, depending on the anesthetic technique used and the preventive and therapeutic Fig.…”
Section: Discussioncontrasting
confidence: 77%
“…Nausea and emesis during regional anesthesia for elective cesarean delivery is widespread, with a reported occurrence of 17-80% of patients experiencing a nausea and/or emesis event [1][2][3][4][5][6][7][8][9][10][11]. Metoclopramide and droperidol are commonly administered to reduce nausea and emesis in patients undergoing spinal anesthesia for cesarean section [1][2][3]12].…”
Section: Introductionmentioning
confidence: 99%
“…(7) where incidence of intraoperative nausea and vomiting by prophylactic ondansetron as compared to placebo group was 10% versus 75%; and 20% incidence rate by prophylactic metoclopramide as observed by Fiujii et al (8) Vasanthakumar et al (9) in their study group concluded that injection ondansetron decreases the incidence of emetic episodes than metoclopramide. However, in our study no stastically significance in the incidence of nausea and vomiting could be observed between the two studied drugs.…”
Section: Discussionmentioning
confidence: 96%